PENGHAPUSAN KEBIJAKAN RINTISAN SEKOLAH BERSTANDAR INTERNASIONAL (RSBI) - Dewi Sendhikasari Dharmaningtias (Sekretariat Jenderal DPR RI, 2013)
Education is not only an important pillar to bring progress to the nation, but also a necessary condition for improving the welfare of the people. Unfortunately, RSBI as a public policy in education is considered to have failed to achieve its goal to improve the quality of education in this country. It is argued in this essay that RSBI againts the 1945 state constitution article 50 paragraph 3 of Law No. 20 2003 is contrary to the Constitution which has guaranteed education for all Indonesian people. Because of this controversy and many criticism, the Constitutional Court has finally revoked the RSBI policy.